2019
DOI: 10.1007/978-3-030-16538-3_2
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals and Applications of Chitosan

Abstract: Chitosan is a biopolymer obtained from chitin, one of the most abundant and renewable material on Earth. Chitin is a primary component of cell walls in fungi, the exoskeletons of arthropods, such as crustaceans, e.g. crabs, lobsters and shrimps, and insects, the radulae of molluscs, cephalopod beaks, and the scales of fish and lissamphibians. The discovery of chitin in 1811 is attributed to Henri Braconnot while the history of chitosan dates back to 1859 with the work of Charles Rouget. The name of chitosan wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 355 publications
(260 reference statements)
0
91
0
Order By: Relevance
“…In their comprehensive reviews, Crini (2015), Yong et al (2015), Kyzas et al (2017), Wang and Zhuang (2017), Desbrières andGuibal (2018), El Halah et al (2018) and Pakdel and Peighambardoust (2018) recently indicated that biosorption onto chitosan was a promising alternative to replace conventional adsorbents used for decolorization purposes, metal chelation or recovery, and organic removal. With nutraceuticals and cosmeceuticals, the water and wastewater treatment field seems to be the next market in the development of chitosan (Morin-Crini et al 2019).…”
Section: Chitosan For Wastewater Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In their comprehensive reviews, Crini (2015), Yong et al (2015), Kyzas et al (2017), Wang and Zhuang (2017), Desbrières andGuibal (2018), El Halah et al (2018) and Pakdel and Peighambardoust (2018) recently indicated that biosorption onto chitosan was a promising alternative to replace conventional adsorbents used for decolorization purposes, metal chelation or recovery, and organic removal. With nutraceuticals and cosmeceuticals, the water and wastewater treatment field seems to be the next market in the development of chitosan (Morin-Crini et al 2019).…”
Section: Chitosan For Wastewater Treatmentmentioning
confidence: 99%
“…In the past three decades, numerous approaches have been studied for the development of cheaper, ecofriendly and more effective biosorbents capable to eliminate pollutants present in synthetic solutions contaminated with a single type of pollutant (Onsoyen and Skaugrud 1990;Peters 1995;Allen 1996;Goosen 1997;Hirano 1997;Ramakrishna and Viraraghavan 1997;Cooney 1999;Blackburn 2004;Gavrilescu 2004;Varma et al 2004;Crini 2005Crini , 2006Bhatnagar and Minocha 2006;Oliveira and Franca 2008;Qu 2008;Gadd 2009;Wang and Chen 2009;Elwakeel 2010;Park et al 2010;Ali 2012;Michalak et al 2013;Katheresan et al 2018;Piaskowski et al 2018). Among the various materials proposed for water and wastewater treatment by biosorption, cross-linked chitosan hydrogels are by far the most widely studied materials, owing not only to their efficiency at eliminating a broad range of pollutants but also to their synthesis that is straightforward and facile (Ravichandran and Rajesh 2013;Liu and Bai 2014;Vandenbossche et al 2015;Yong et al 2015;Muya et al 2016;Nechita 2017;Pakdel and Peighambardoust 2018;Morin-Crini et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…During the last two decades there has been a fast rise in the use of chitosan as bioflocculant, and in the development of new chitosan-based materials, e.g., grafted chitosans, composites and hybrid materials, for direct bioflocculation processes. The main potential applications are in water and wastewater treatment, sludge dewatering and harvesting of microalgae, and dissolved air flotation (Chong 2012;Lee et al 2014;Yang et al 2016;Morin-Crini et al 2019;Vidal and Moares 2019). Table 1 describes the main characteristics and properties of chitosan applied to flocculation.…”
Section: Direct Bioflocculation Using Chitosanmentioning
confidence: 99%
“…The main challenge of palm oil-producing countries is the production of palm oil mill effluents in large amounts. In Malaysia alone, approximately 50 to 75 million tons of Roberts (1992), No and Meyers (1995), Peters (1995), Goosen (1997), Kurita (1998Kurita ( , 2006, Ravi Kumar (2000), Domard and Domard (2001), Dutta et al (2004), Vårum and Smidsrød (2004), Rinaudo (2006), Li et al (2008), Crini et al (2009a, b), de Alvarenga (2011), Sudha (2011), Nwe et al (2011), Teng (2016, Nechita (2017), Morin-Crini et al (2019), Vidal and Moraes (2019) Main characteristics and properties Raw chitosan for water treatment applications: low-cost product. Chitin: is a renewable resource obtained from industrial by-products Non-toxic, biocompatible and biodegradable Eco-friendly biopolymer; ecologically acceptable product Linear amino-polysaccharide with high nitrogen content; weak base and powerful nucleophile Hydrophilic biopolymer with high reactivity Reactive amino and hydroxyl groups for modification Polyelectrolyte at acidic pH with high charge density: a polycationic biopolymer Ionic conductivity Gelation ability, adhesivity, film-forming ability Ability to form hydrogen bonds and other non-covalent interactions Ability to encapsulate, entrapment properties Chelation, ion-exchange and adsorption properties Removal of pollutants or pollutions, e.g.…”
Section: Palm Oil Mill Effluentsmentioning
confidence: 99%
“…This insolubility enormously affects the scalability of the processes for chitinbased products (1,2). Due to the inertness and crystallinity of chitin, chemical conversion to acid-soluble chitosan requires drastic conditions, rendering the process unsustainable and not ecological (3,4). The identification of chitinolytic enzymes of microbial origin, enabling chitin conversion under mild conditions, is thus highly sought after.…”
mentioning
confidence: 99%